Hubungan Kepatuhan Pemasangan Infus dengan Pengetahuan Pencegahan Phlebitis Perawat di RS TK III dr. Sindhu Trisno - Dhea Juniarni; Arniawan; Siti Yartin (Universitas Widya Nusantara, 2025)
Phlebitis was one of the most common complications resulting from intravenous infusion, therefore nurses’ compliance with standard operating procedures for infusion insertion was an important factor in phlebitis prevention and was influenced by nurses’ knowledge. This study aimed to determine the relationship between nurses’ compliance with intravenous infusion insertion and knowledge of phlebitis prevention at Tk III Dr. Sindhu Trisno Hospital. This study employed a quantitative design with a cross-sectional approach and was conducted from January 17 to March 27, 2025. The study population included all 69 nurses working in the inpatient wards, and total sampling was applied. Data were collected using a knowledge questionnaire and a compliance observation checklist based on the standard operating procedures for infusion insertion. Data were analyzed using univariate and bivariate analyses with the chi-square test at a significance level of p < 0.05. The univariate analysis showed that most nurses had good knowledge of phlebitis prevention (76.8%) however, the majority were not compliant with infusion insertion procedures (69.6%). The bivariate analysis demonstrated a significant relationship between compliance with intravenous infusion insertion and nurses’ knowledge of phlebitis prevention (p < 0.05). It was concluded that there was a significant relationship between compliance with infusion insertion and nurses’ knowledge of phlebitis prevention at Tk III Dr. Sindhu Trisno Hospital; therefore, improving knowledge through continuous education and training was necessary to enhance compliance.